Deleterious Mechanical Deformation Selects Mechanoresilient Cancer Cells with Enhanced Proliferation and Chemoresistance - Kuan Jiang; Su Bin Lim; Jingwei Xiao; Doorgesh Sharma Jokhun; Menglin Shang; Xiao Song; Pan Zhang; Lanfeng Liang; Boon Chuan Low; G.V. Shivashankar; Chwee Teck Lim (Advanced Science, 2023)
Abstract Cancer cells in secondary tumors are found to form metastases more efficiently as compared to their primary tumor counterparts. This is partially due to the unfavorable microenvironments encountered by metastasizing cancer cells that result in the survival of a more metastatic phenotype from the original population. However, the role of deleterious mechanical stresses in this change of metastatic potential is unclear. Here, by forcing cancer cells to flow through small capillary‐sized constrictions, it is demonstrated that mechanical deformation can select a tumor cell subpopulation that exhibits resilience to mechanical squeezing‐induced cell death. Transcriptomic profiling reveals up‐regulated proliferation and DNA damage response pathways in this subpopulation, which are further translated into a more proliferative and chemotherapy‐resistant phenotype. These results highlight a potential link between the microenvironmental physical stresses and the enhanced malignancy of metastasizing cancer cells which may be utilized as a therapeutic strategy in preventing the metastatic spread of cancer cells.